Psihosocijalni čimbenici na radnom mjestu i zadovoljstvo radnika u hotelijerstvu - Kirin, Snježana (Array, 2020)
Job satisfaction is a set of positive or negative feelings employees experience in their work, and they relate to various factors: co-workers, job description, superiors, pay, working conditions, hours, promotion, acknowledgement, status, success, responsibility, safety, possibility for further development and other.Employee satisfaction was investigated using the close-ended survey questionnaire method and it included the following employees of a hotel: server, waiter, sous-chef and chef. The survey questionnaire consisted of 14 parts and a total of 24 questions, including both general questions and those directly affecting the employees’ satisfaction at work (pay, hours, safety at work, work place, organisation, awareness and other). The analysis of the answers showed that the employees are satisfied with the work place on all counts, with the employee satisfaction percentage ranging from 77% to 100%, depending on the question.